NETIZENS' RESPONSE TO THE IKN ISSUE: A NETNOGRAPHY STUDY ON TEMPODOTCO 'S YOUTUBE CHANNEL BOCOR ALUS - Fadya Azizah Al Virandra; Kartikawati, Dwi (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to analyze the response of netizens to the issue of moving the National Capital City (IKN) in the episode